Sailing video-imagery: Impacts on imagery ability - Gapin, J.; Herzog, T. (Journal of Imagery Research in Sport and Physical Activity, 2014)
The purpose of this study was to investigate the impact of a standardized mental practice tool incorporating principles of video, modeling, and traditional-imagery,on the imagery ability of competitive college sailors. A quasi-experimental method using a quantitative pre-test/post-test design was administered with a convenience sample of collegiate sailors recruited via the Internet. An integrated video-imagery intervention was compared with a traditional verbal intervention to measure each intervention`s impact on imagery ability. The Vividness of Movement Imagery Questionnaire-2 (VMIQ-2) was used to assess external visual imagery, internal visual imagery, and kinesthetic imagery. Exposure to video-imagery resulted in significant improvement of external visual, internal visual, and kinesthetic imagery abilities. There was no significant difference between improvements from video-imagery versus traditional-imagery. Future studies should explore best combinations of imagery and observation techniques, and efficacious elements of each